LEARNING AND TEACHING RUSSIAN LANGUAGE IN CHINA AND TAIWAN: PAST AND PRESENT - Lidiya Z. Tenchurina; Hsi-mei Li (Russian State Vocational Pedagogical University, 2016)
The paper presents the main study results on the analysis of processes of establishing and development of Russian language studies and Russian language training practices in mainland China and Taiwan since the early XVIII century until now. Basing on the postulates of the social-and-cultural, systemic and historical, historiographical and axiological approaches, the authors attempt to describe the development of the theory and practice of teaching and studying Russian as a foreign language (RFL) with a view to form a complete picture of the past and present of the Russian language in China and Taiwan, to evaluate the role and importance of the Russian language, primarily, in the socialand-cultural, as well as in the social-and-political and even economic aspects, not only from historic perspectives but also in terms of the future development - basing on evolving cooperation between Russia, on the one hand, and China and Taiwan - on the other. Methods. The main applied research methods are the comparative-historical and historical-and-logical analysis, historical reconstruction methods, systematization, theoretical generalizations and, partly, prediction. Scientific novelty. The novelty of the study lies in the fact that for the first time in the broader period (1700-2000 s) it offers a generalized description of the establishment and development of Russian studies and practice of teaching the Russian language in China and Taiwan. Practical significance. The implementation of the research outcomes can be useful due to a possibility of carrying on its basis of new studies on the problems of Russian philology and teaching Russian as a foreign language, the history of pedagogy and education, and comparative pedagogy (comparative linguistics).